Mobilization – a new concept in analysing transport system dynamics, or how security and mobility are melded to trigger change. Issue 1 (2nd January 2021) - Schäfer, Philip Jan
ABSTRACT: This paper outlines and illustrates the concept of mobilization in the case of the Cheonggyecheon project and the Seoul 2030 agenda. Mobilization outlines how mobility issues are identified, defined and presented to change transport systems by shaping the underlying discourse with elite perceptions transferred into socially accepted constructions of reality. In form of mobilizations decision makers construct threats to the sustainability of transport systems and proclaim the requirement for immediate action – for example in form of large infrastructure projects. Therefore mobilization identifies and theoretically models the dynamic connections between movement, power and politics. An analysis of the discursive structures that frame the Cheonggyecheon project and the Seoul 2030 agenda is conducted to investigate how single representations of exceptional measures in form of mobilizations legitimize and stabilize a sustainability logic resulting in the transformation of transport systems.